FNDC5 Causes Resistance to Sorafenib by Activating the PI3K/Akt/Nrf2 Pathway in Hepatocellular Carcinoma Cells - Liu, Huayuan; Zhao, Lei; Wang, Mengya; Yang, Kexin; Jin, Zhipeng; Zhao, Chengjian; Shi, Guangjun (Frontiers in Oncology, 2022)
In this study, we aimed to reveal the resistance mechanism of hepatocellular carcinoma (HCC) cells to sorafenib by exploring the effect of FNDC5 on sorafenib-induced ferroptosis in HCC cells. We compared the expression level of FNDC5 between sorafenib-resistant and sorafenib-sensitive HCC cell lines and the level of ferroptosis between the groups after treatment with sorafenib. We knocked down FNDC5 in drug-resistant cell lines and overexpressed it in sorafenib-sensitive HCC cell lines to further demonstrate the role of FNDC5 in sorafenib-induced ferroptosis. Using PI3K inhibitors, we revealed the specific mechanism by which FNDC5 functions. In addition, we verified our findings obtained in in vitro experiments using a subcutaneous tumorigenic nude mouse model. The findings revealed that FNDC5 inhibits sorafenib-induced ferroptosis in HCC cells. In addition, FNDC5 activated the PI3K/Akt pathway, which in turn promoted the nuclear translocation of Nrf2 and increased the intracellular antioxidant response, thereby conferring resistance to ferroptosis. Our study provides novel insights for improving the efficacy of sorafenib.